Penduduk Usia Lanjut Sebagai Konsekuensi DemograflsAkebat Peningkatan Harapan Hedup - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT This article addresses the life expectancy at birth in the context of predicting the future problem concerning the population aging in Indonesia. Levels, trends and differentials of life expectancy at births are presented according to the province. A simple interpretation of life expectancy at birth is presented in the manner of its relevancy for comparing the level between region and predicting the future longevity of a baby birth in the given year. There is a strong evidence that average of age death can be longer than a formal number of life expectancy at birth reported by national statistical office. Using both a projection and prediction Indonesia has to able to address the dramatic increase of aging population for the next 25 years. Three areas of policy concems should be addressed seriously: a) the quality of future aging population as a human resource